ANALISIS RETRIBUSI PARIWISATA PANTAI UNTUK MENINGKATKAN PAD KABUPATEN GUNUNGKIDUL PADA MASA PANDEMI COVID-19 - Dwi Wulandari; Priyastiwi Priyastiwi (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2022)
Gunungkidul is famous for its coastal tourism, where it affects its Regional Revenue (PAD). Although, it started getting paralyzed for pandemic Covid 19. This study aims to measure how much Gunungkidul coastal tourism retribution contributes to Regional Revenue (PAD) increase, and to find out efforts taken to increase PAD through coastal tourism retribution during pandemic. This study uses quantitative descriptive research approach. The object of this study is Gunungkidul Government. Besides, this study uses primary and secondary research data. The data analysis methods uses in this study are contribution analysis, descriptive analysis and data analysis of the Miles and Huberman model. Based on the study result, it states that Gunungkidul coastal tourism retribution contributes less than 10% to Gunungkidul Regional Revenue (PAD), which is not quite significant. Several strategies were used by Gunungkidul Government in order to increase the Regional Revenue (PAD) during pandemic, namely promotion through social medias, e-ticketing for online ticket order and payment, as well as health protocol implementation in tourism sites.